Audit Atas Perpajakan Sebagai Instrumen Pengendalian Resiko Kepatuhan Pajak Pada Perusahaan (Studi Kasus: PT. AAC) - Nur Asma (Jaanur Elbarik Indonesia, 2026)
The emphasis of the abstract is primarily on the results of tax audits, which are an important instrument in ensuring corporate tax compliance with applicable tax regulations. Tax compliance not only covers the accuracy of tax calculations, but also the accuracy of tax procedures and administration. This paper aims to analyze the role of tax audits as an instrument for controlling tax compliance risks in companies using the case study of PT AAC. The research method used is a qualitative descriptive approach through literature study and analysis of Tax Court decisions. The results of the discussion show that tax audits play an important role in identifying tax non-compliance risks and ensuring formal and material compliance. The PT AAC case study shows that procedural errors in the tax audit process can result in the cancellation of the Tax Assessment Letter for Underpayment (SKPKB), thus emphasizing the importance of accurate audit procedures in controlling corporate tax compliance risks